Teachers’ and Students’ Experiences of Simultaneous Teaching in an International Distance and On-Campus Master’s Programme in Engineering - Oleg Popov (Athabasca University Press, 2009)
Swedish universities frequently offer campus-based education as well as online courses, a system commonly referred to as dual mode. This paper analyses some challenging pedagogical aspects of a master’s programme in engineering developed and delivered simultaneously online and on campus. Course evaluations, questionnaires, and interviews with the programme teachers were the main instruments used in this study. Activity theory was used as a theoretical framework for data collection and analysis. The study evidences the nature of problems experienced by on-campus and distance students as well as conflicts of interest and expectations existing between these two student groups. Teaching simultaneously in two modes demands extra effort from the course teachers, who are aware of the problems related to pedagogical communication needed by both groups. Though teaching in the dual mode offers economic benefits for the department, the simultaneous mode of teaching is experienced as problematical by both groups of students, with distance students appearing to be more disadvantaged in the programme.